Development of Institution Structure of Agriculture Resources Management at Pesantren - Septalina Pradini; Hadi Alikodra; Hasim Hasim; Tri Pranadji (Wacana Journal of Social and Humanity Studies, 2017)
Multirole of pesantren demand are very complex and dynamic in human development and agriculture development. Pesantrens who have noble values, the spiritual capital as well as agricultural resources are expected to drive the development of agriculture. However, the problem complexity that exist bring pesantren to changes overall and continuously to achieve its goals. This study aims to identify the key elements of the development of the institutional structure of agricultural resource management at pesantren, and also strategy formulation as well as institutional model implementation. Analysis of the institutional structure used Interpretive Structural Modeling (ISM), and prioritizing implementation models strategies used Exponential Comparative Method (ECM). Financing institutions identified as key elements of institutional structures at pesantren has agricultural resources. Pesantren as social institutions have the potential of agricultural resources managed by the cooperative venture or other productive enterprises. The agency is highly dependent on the financial institutions supporting with a particular scheme in order to promote the sustainability of educational activities and business management that grew up in pesantren. Institutional management of agricultural resources is reinforced by economic institutional community based on faith and good deeds that create a balance of material and spiritual well as the interests of the individual and society. Priority implementation strategy including the competency development of HR pesantren, pesantren leadership cadre and the development of vision-mission in accordance with the paradigm of sustainable development.